PERANAN POS SAHABAT PEREMPUAN DAN ANAK DALAM MEMINIMALISIR KEKERASAN DALAM RUMAH TANGGA - Hengki Satrianta; Anna Rufaidah; Afiatin Nisa; Sabrina Dachmiati (Musawa: Journal for Gender Studies, 2022)
Domestic violence is a hotly discussed issue. Its coverage in the mass media is constantly conveyed to the public. From any point of view, the terms "stop domestic violence" and "zero tolerance for domestic violence" must be echoed. One of the efforts of the DKI Jakarta provincial government is to establish the Pos Sahabat Perempuan dan Anak (Pos SAPA) which is expected to be a service forum related to domestic violence. This article aims to describe the role of Pos Sahabat Perempuan dan Anak to minimize domestic violence. This research is a qualitative descriptive study. The informants in this study consisted of five members of the Pos Sahabat Perempuan dan Anak at Universitas Indraprasta PGRI. Data were collected through interview techniques, observation, and documentation notes. data were analyzed descriptively through content analysis. The results of the study show that the role of the Pos Sahabat Perempuan dan Anak in minimizing domestic violence is pursued through preventive, curative, and promotive actions. The results of this study are expected to be able to become a new design for research in the field of domestic violence studies.